Lower Urinary Tract Symptoms in Subjects with Subclinical Cerebral White Matter Lesions - Chi-Hang Yee; Ching Leung; Yuki Yu-Ting Wong; Sylvia Lee; Jenny Li; Pauline Kwan; Winnie Chiu-Wing Chu; Vincent Chung-Tong Mok; Chi-Fai Ng (Journal of Aging Research)
Aim. We assessed the impact of cerebral white matter lesions (WMLs) on lower urinary tract symptoms in subjects with normal neurological and cognitive function. Methods. A cohort of community-dwelling subjects aged ≥65 years were recruited to undergo MRI brain assessment. WMLs were graded using the Fazekas scale from 0 to 3. A separate telephone interview was carried out to assess the urinary symptoms in these subjects using the questionnaire Overactive Bladder-Validated 8-Question Awareness Tool (OAB-V8). Results. 800 community-dwelling elderly subjects were recruited to undergo MRI brain. In this cohort, 431 subjects responded to the telephone interview concerning their urinary symptoms. Among the respondents, 21.1% did not exhibit any WML on their MRI brain. Most of the subjects (52.6%) exhibited grade 1 WML. On logistic regression, age was found to be positively correlated with the Fazekas score (correlation coefficient 0.203, p≤0.01). Using a cutoff of 8 on OAB-V8, 22% of the respondents experienced OAB. Presence of WML, hypertension, or diabetes mellitus was not found to be correlated with storage urinary symptoms or OAB-V8 total score. Multiple logistic regression analysis did not show the presence of WML to be associated with the diagnosis of OAB (adjusted OR 1.13, 95% CI 0.65–1.96, p=0.659). Conclusions. WML is associated with age and is common in the elderly population. Mild WML is subclinical, with no obvious neurological and urinary symptoms. Our cohort did not demonstrate a relationship between WML and lower urinary tract symptoms.